Relationships between Particle Size and Fracture Energy for Single Particle Crushing [Translated]† - Yoshiteru Kanda (KONA Powder and Particle Journal, 2014)
An experimental study of single-particle crushing at slow compression rate was carried out for two kinds of glassy and five kinds of natural materials. The specimens were almost spherical particles of 0.5 to 3.0 cm in diameter. The relationships between particle size and fracture energy (strain energy) were calculated by using the results of the size effect ranging from about 10 cm to 0.0030 cm of single particle crushing, as shown in the previous papers. The experimental results are summarized as follows: 1) The fracture energies obtained were larger than the values calculated from the theoretical equations for limestone, marble and gypsum. 2) For natural materials, the specific fracture energies rapidly increased with decreasing particle size within the range of particle size smaller than about 500 µm.† This report was originally printed in KAGAKU KOGAKU RONBUNSHU, 10(1), 108-112 (1984) in Japanese, before being translated into English by KONA Editorial Committee with the permission of the editorial committee of the Soc. Chemical Engineers, Japan.